The roles of ulama' in Kedah - Mat Zain, Farid; Zakariya, Hafiz (IIUM Press, International Islamic University Malaysia, 2017)
This book aims at presenting a Muslim religious scholar who could be regarded as a Muslim revivalist in Kedah during the first half of the 20th century named Wan Sulaiman Wan Sidek. He was the contemporary of Tuan Husain Nasir al-Mas’udi al-Banjari known as Tuan Husain Kedah. These two Muslim religious scholars were very well known because both were very active and prolific although Wan Sulaiman joined the government administration and Tuan Husain remained as an independent religious scholar and teacher. The personality of Wan Sulaiman is presented in the chapter on his biography. His great contributions are studied and presented in many aspects. In the Kedah public administration he contributed through his public position as Shaykh al-Islam. In Islamic education, Wan Sulaiman founded the madrasah education system different from the pondok education system found in Kedah and in Patani.